EIN2-mediated signaling is involved in pre-invasion defense in Nicotiana benthamiana against potato late blight pathogen, Phytophthora infestans. (3rd April 2017) - Rin, Soriya; Mizuno, Yuri; Shibata, Yusuke; Fushimi, Mayuka; Katou, Shinpei; Sato, Ikuo; Chiba, Sotaro; Kawakita, Kazuhito; Takemoto, Daigo
ABSTRACT: Nicotiana benthamiana ABCG1 and ABCG2 are ABC transporters which are probably involved in the export of capsidiol, the major phytoalexin of Nicotiana species. While capsidiol export by these transporters plays an essential role in post-invasion defense against Phytophthora infestans, they also export unidentified antimicrobial compound(s) involved in pre-invasion defense. In this study, promoter activity of NbABCG2 (P abcg2a ) was analyzed using a GFP marker. Expression of GFP under the control of P abcg2a was significantly increased by co-expression with the INF1 elicitor from P. infestans . Disruption of the ethylene-responsive GCC box in P abcg2a compromised INF1-induced activation of P abcg2a . Consistently, penetration by P. infestans was increased by gene-silencing of NbEIN2, the key ethylene-signaling component, suggesting the involvement of ethylene for pre-invasion defense of N. benthamiana .